Social correlates of ownership and utillization of insecticide and utilization of insecticide treated bed-nets for Malaria among women of child bearing ages Mozambique - Forty, James; Palamuleni, Martin E (Penerbit Universiti Kebangsaan Malaysia, 2021)
Insecticide Treated Bednets is one of the interventions in combating malaria which is one of the major public health challenges in Africa. The aim of this study is to assess the prevalence and determinants of treated mosquito bed-nets possession and utilization among women of child-bearing ages in Mozambique. The study is based on secondary analysis of 6184 women who were interviewed in the 2018 Malaria Indicator Survey. Data was analyzed using descriptive statistics, chi-square test and logistic regressions. The study reveals that 82.1% of the women know that sleeping under treated mosquito bed-net prevents malaria, 90.2% of the women have treated mosquito nets and 77.0% of the women slept under treated mosquito bed-net in the last night prior to the survey. Multivariate logistic regression indicates that type of province of residence, level of education, having radio in the household, wealth index, knowledge that treated mosquito net protects from malaria and seen or heard of malaria messages in last six months prior to survey were significantly associated with ownership of treated mosquito bed-nets. Meanwhile, education, household with radio and age af household head were significantly related to the use of Insecticide Treated Net.Therefore, there is need for interventions for social behaviour change; wide spread of malaria specific messages and continued free distribution of ITNs to poor households. This would help to increase the ownwership and use of insecticide treated bed-nets.As a policy measure, information, education and communication programmes should be intensified, particularly targeting men. Patriarch structures that reinforce power imbalance between men and women should be dismantled.